Digital emotion regulation interventions for patients with congenital heart disease: a randomized clinical trial - Prüßner, Luise; Hartmann, Steffen; Ehmann, Anna-Lena; Barnow, Sven; Bauer, Ulrike M. M.; Helm, Paul C. (JAMA network open, 2025)
Congenital heart disease (CHD) is associated with emotional distress and reduced quality of life, yet evidence-based psychosocial treatments are limited. Digital emotion regulation interventions may offer a scalable solution.To evaluate the effectiveness of tailored and general digital emotion regulation interventions compared with usual care for patients with CHD.This 3-arm, parallel-group randomized clinical trial was conducted from August 5, 2022, to October 21, 2024. Adults (≥18 years) with CHD were recruited nationwide in Germany.Participants were randomized to a 4-week digital program with daily exercises to improve emotion regulation flexibility, delivered in a tailored or general format, or to usual CHD care.The primary outcome was change in emotion regulation difficulties. Secondary outcomes were the changes in emotion regulation repertoire, well-being, life satisfaction, anxiety, depression, stress, and illness identity. Analyses followed an intention-to-treat approach.Of 1043 individuals screened, 524 were randomized (mean [SD] age, 35.2 [12.7] years; 364 women [69.5%]). At postintervention, the tailored program reduced emotion regulation difficulties compared with usual care (Cohen d = −0.45; 95% CI, −0.72 to −0.18; P = .001), whereas the general program did not. For secondary outcomes, the tailored program improved emotion regulation repertoire (Cohen d = 0.49; 95% CI, 0.18-0.78; P < .001), well-being (Cohen d = 0.39; 95% CI, 0.11-0.67; P = .006), life satisfaction (Cohen d = 0.37; 95% CI, 0.08-0.66; P = .01), anxiety (Cohen d = −0.38; 95% CI, −0.63 to −0.13; P = .003), depression (Cohen d = −0.40; 95% CI, −0.68 to −0.12; P = .005), and stress (Cohen d = −0.54; 95% CI, −0.86 to −0.22; P < .001), whereas the general program reduced stress only (Cohen d = −0.32; 95% CI, −0.58 to −0.05; P = .02). At follow-up, all primary and secondary gains for the tailored program were maintained, whereas the general program improved emotion regulation difficulties, anxiety, depression, and stress. Direct comparisons of the active interventions showed no difference in the primary outcome but greater gains in emotion regulation repertoire favoring the tailored program (postintervention: Cohen d = 0.26; 95% CI, 0.07-0.45; P = .007; follow-up: Cohen d = 0.33; 95% CI, 0.11-0.55; P = .004).In this randomized clinical trial of adults with CHD, a tailored digital intervention improved emotion regulation and psychosocial outcomes at postintervention and at follow-up, whereas a general program showed more delayed benefits. These findings highlight the potential of tailored digital emotion regulation tools to meet the specific mental health needs of people living with chronic medical conditions.ClinicalTrials.gov Identifier: NCT05862909
Gesehen am 25.02.2026